GABRINOX-2 protocol: a French, prospective, multicentre, randomised phase II trial evaluating gemcitabine/nab-paclitaxel followed by FOLFIRINOX versus FOLFIRINOX alone as first-line treatment for metastatic pancreatic cancer - Sophie Gourgou; Fabienne Portales; Marc Ychou; Catherine Fiess; Eric Assenat; Fanny Salasc (BMJ Open)
Introduction Pancreatic adenocarcinoma is a major public health concern due to its high metastatic potential and poor prognosis. However, treatment options remain limited. A promising therapeutic strategy involves the sequential administration of standard therapies. In a previous phase Ib-II trial, we evaluated a sequential regimen of gemcitabine plus nab-paclitaxel (GEMBRAX) followed by FOLFIRINOX (FFX), which improved median overall survival (OS), progression-free survival and objective response rate (ORR), with acceptable toxicity. This phase II randomised trial will assess the efficacy of GEMBRAX followed by FFX compared with FFX alone as a first-line treatment for metastatic pancreatic cancer (mPC).Methods and analysis The GABRINOX-2 (GemcitabineABRaxaneIRInotecanOXaliplatine-2) study is an ongoing prospective, multicentre, randomised phase II trial. A total of 162 patients with mPC will be randomised (1:1) to receive GEMBRAX treatment followed by FFX (arm A) or FFX alone (arm B). The primary objective is to compare the efficacy of GEMBRAX followed by FFX with FFX alone as a first-line treatment for mPC. Secondary objectives include treatment tolerability, ORR, disease control rate, OS and patient quality of life. Additionally, we aim to identify novel biomarkers associated with treatment response through the analysis of circulating tumour DNA and assess the messenger RNA signature’s predictive value for OS based on treatment approach.Ethics and dissemination This study was approved by the comité de protection des personnes Ile de France III (26 July 2021) and the French National Agency for the Safety of Health Products (17 September 2021). It will be carried out in accordance with European Reglementation 536/2014 on clinical trials, the Declaration of Helsinki, Good Clinical Practice guidelines and the French Public Health Code. The results will be published in peer-reviewed journals and presented at national and international conferences.Trial registration number This trial has been registered on euclinicaltrials.eu (EU 2023-508594-84-00) and on clinicaltrials.gov (NCT05065801).